Simulasi In Silico Integrasi EGF ke Lactobacillus rhamnosus GG melalui CRISPR-Cas9 Sebagai Probiotik Terapeutik Ulkus Kronis: In Silico Simulation of EGF Integration Into Lactobacillus rhamnosus GG Via CRISPR-Cas9 For Therapeutic Probiotics For Chronic Ulcers - Arini Rizakiya; Alifah Rahma Mutiasari; Medina Fiamanella; Mutimmah Mutimmah; Afryansyah Afryansyah; Aji Jumiono; Erna Puspasari (Universitas Djuanda, 2026)
Chronic wounds are a health problem characterized by failure to heal within four weeks and the potential for physical and psychological complications. One important factor in wound healing is the availability of Epidermal Growth Factors (EGF), which is often disrupted in chronic wounds. This study aims to investigate in silico the mechanism of CRISPR-Cas9-based genetic engineering of Lactobacillus rhamnosus GG bacteria as a therapeutic probiotic that produces EGF for the healing of chronic ulcer. The research method used a bioinformatics approach that included genetic homology analysis, guide RNA design, recombinant plasmid construction, mRNA secondary structure prediction, protein physicochemical property analysis, and EGF protein tertiary structure modeling. The result showed that the EGF gene has no significant similarity with the Lactobacillus rhamnosus GG genome, the designed gRNA had good specificity and cutting efficiency, and the gene construction was potentially stable and expressed. The stimulated EGF protein showed good three-dimensional structure quality with exposed active residues. Overall, this study shows that the in silico approach has the potential to become the basis for the development of CRISPR-Cas9-based engineered probiotics as an alternative therapy for chronic wound healing.